The binary lottery procedure does not induce risk neutrality in the Holt-Laury and Eckel-Grossman tasks - Jörg Oechssler; Andis Sofianos (University of Heidelberg, Department of Economics, 2019)
We test whether the binary lottery procedure makes subjects behave as if they are risk neutral in the Holt-Laury and Eckel-Grossman tasks. Depending on the task we find that at most a third of subjects behave as if risk neutral. In fact, when we compare the distribution of choices we find no significant difference to earlier experiments in the same lab that did not use the binary lottery procedure.
urn:nbn:de:bsz:16-heidok-264389
Keywords: C91; C81; 330; risk elicitation; binary lottery procedure; experimental economics